STUDI IDENTIFIKASI USER DAN PROGRAM ARSITEKTUR PADA PERENCANAAN FASILITAS PENGOLAHAN LIMBAH TEKSTIL DI JAKARTA BARAT - Andrew William Philip Lika; Irene Syona Darmady (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2026)
The growth of the textile industry in West Jakarta has shown a significant increase along with the expansion of fast fashion trends and the ease of distribution through e-commerce platforms. This rise in production has directly contributed to an increasing volume of textile waste, particularly within small- and medium-scale industries that generally lack adequate waste management systems. This condition creates environmental challenges as well as the need for facilities capable of managing and optimizing textile waste through sustainable approaches. This study aims to identify user characteristics and formulate appropriate architectural programs for the planning of a textile waste processing facility in West Jakarta. The research employs a qualitative approach through literature studies and field observations to understand existing conditions and actual needs within the study area. The findings indicate that the primary users of the facility include textile industry actors, waste processing technicians, creative communities, educational institutions, and the general public. User activities are categorized into three main groups: technical, educational, and creative activities, each requiring spaces with distinct characteristics while remaining functionally integrated. The synthesis of the findings emphasizes that the architectural program should integrate industrial, educational, and upcycling-based creative functions within an adaptive spatial system. The application of a regenerative architectural approach is expected to produce a facility that not only functions technically but also generates positive environmental, social, and economic impacts on the surrounding area. Keywords: facility; program; regenerative; user; waste Abstrak Pertumbuhan industri tekstil di Jakarta Barat menunjukkan peningkatan signifikan seiring berkembangnya tren fast fashion dan kemudahan distribusi melalui platform e-commerce. Peningkatan produksi tersebut berdampak langsung pada bertambahnya volume limbah tekstil, terutama pada industri skala kecil dan menengah yang umumnya belum memiliki sistem pengolahan limbah yang memadai. Kondisi ini menimbulkan permasalahan lingkungan sekaligus kebutuhan akan fasilitas yang mampu mengelola dan mengoptimalkan limbah tekstil secara berkelanjutan. Penelitian ini bertujuan untuk mengidentifikasi karakteristik pengguna serta merumuskan program arsitektur yang tepat dalam perencanaan fasilitas pengolahan limbah tekstil di Jakarta Barat. Penelitian menggunakan pendekatan kualitatif melalui metode studi literatur dan observasi lapangan untuk memahami kondisi eksisting dan kebutuhan nyata di kawasan penelitian. Hasil penelitian menunjukkan bahwa pengguna utama fasilitas meliputi pelaku industri tekstil, tenaga teknis pengolahan limbah, komunitas kreatif, lembaga pendidikan, serta masyarakat umum. Aktivitas pengguna terbagi ke dalam tiga kelompok utama, yaitu aktivitas teknis, edukatif, dan kreatif, yang masing-masing membutuhkan ruang dengan karakteristik berbeda namun saling terintegrasi. Sintesis hasil studi menegaskan bahwa program arsitektur perlu menggabungkan fungsi industri, edukasi, dan aktivitas kreatif berbasis upcycling dalam satu sistem ruang yang adaptif. Penerapan pendekatan arsitektur regeneratif diharapkan mampu menciptakan fasilitas yang tidak hanya berfungsi secara teknis, tetapi juga memberikan dampak positif bagi lingkungan, sosial, dan ekonomi kawasan.